Karakteristik Individual Perawat terhadap Kenyamanan dan Kepuasan Proses Interaksi Pelayanan Keperawatan: Individual Characteristics of Nurses on Comfort and Satisfaction of the Nursing Service Interaction Process - Syafrisar Meri Agritubella; Yulastri Arif; Esi Afriyanti (Fakultas Keperawatan Universitas Andalas, 2017)
Comfort and satisfaction in service are the reasons why patients choose the same hospital when they need treatment or come home for physical discomfort, psycho-spiritual, environmental and socio-cultural. Patient satisfaction in some areas is low with average patient satisfaction about 64,3% while according to Kemenkes (2012) patient satisfaction standard to treatment is more than 90%. This study aims to describe and analyze the comfort and satisfaction of patients in the process of interaction nursing service in RSUD Petala Bumi Year 2016. This type of research is an analytic description with a sample of 41 implementing nurses who are in Installation of inpatient. The results of the univariate analysis showed that most of the nurses were in the Early Adult age group (26-35 years) and female gender. More than half the nurses are DIII Nursing and duration of less than 5 years. The result of patient's comfort in interaction process more than half was in comfortable category (52,03%), and patient satisfaction in interaction process more than half of patient was in satisfied category (72,36%.). Bivariate analysis shows the relationship between the long characteristics of nurses working with the comfort and satisfaction of patients in the interaction process of nursing service. It was concluded that the duration of nurse work is an individual factor that gives comfort and satisfaction of the patient in interaction process of nursing service. It is expected that the hospital management consider the individual factors of the nurse as one of the factors that can affect the comfort and satisfaction of patients in the hospital and provide motivation to the old nurses in providing quality nursing services.